Artificial light at night confounds broad‐scale habitat use by migrating birds. (9th January 2018) - McLaren, James D.; Buler, Jeffrey J.; Schreckengost, Tim; Smolinsky, Jaclyn A.; Boone, Matthew; Emiel van Loon, E.; Dawson, Deanna K.; Walters, Eric L.
Abstract: With many of the world's migratory bird populations in alarming decline, broad‐scale assessments of responses to migratory hazards may prove crucial to successful conservation efforts. Most birds migrate at night through increasingly light‐polluted skies. Bright light sources can attract airborne migrants and lead to collisions with structures, but might also influence selection of migratory stopover habitat and thereby acquisition of food resources. We demonstrate, using multi‐year weather radar measurements of nocturnal migrants across the northeastern U.S., that autumnal migrant stopover density increased at regional scales with proximity to the brightest areas, but decreased within a few kilometers of brightly‐lit sources. This finding implies broad‐scale attraction to artificial light while airborne, impeding selection for extensive forest habitat. Given that high‐quality stopover habitat is critical to successful migration, and hindrances during migration can decrease fitness, artificial lights present a potentially heightened conservation concern for migratory bird populations.